Biogel scavenging slows the sinking of organic particles to the ocean depths - Uria Alcolombri; Alon Nissan; Jonasz Słomka; Sam Charlton; Eleonora Secchi; Isobel Short; Kang Soo Lee; François J. Peaudecerf; Dieter A. Baumgartner; Andreas Sichert; Uwe Sauer; Anupam Sengupta; et al. (Nature Communications)
Abstract One of Earth’s largest carbon fluxes is driven by particles made from photosynthetically fixed matter, which aggregate and sink into the deep ocean. While biodegradation is known to reduce this vertical flux, the biophysical processes that control particle sinking speed are not well understood. Here, we use a vertical millifluidic column to video-track single particles and find that biogels scavenged by particles during sinking significantly reduce the particles’ sinking speed, slowing them by up to 45% within one day. Combining observations with a mathematical model, we determine that the mechanism for this slowdown is a combination of increased drag due to the formation of biogel tendrils and increased buoyancy due to the biogel’s low density. Because biogels are pervasive in the ocean, we propose that by slowing the sinking of organic particles they attenuate the vertical carbon flux in the ocean.